Analisis Penerapan Kebijakan Moneter Suku Bunga Jangka Pendek pada Variabel-variabel Endogen MakroEkonomi Indonesia - Sari Damayanti (Bina Nusantara University, 2014)
This study analyzed the impact of the implementation of monetary policy through short-term interest rates setting on the variation that occurs in the endogenous variables of Indonesian macro economy in the period of 2000-2009 by implementing the Structural Vector Autoregressive approach (SVAR) which is the development of Vector Autoregressive (VAR) modelling with Eviews program. By careful examination of the results, this study indicates that the value of interest rate changes is significantly associated with shocks that are associated with monetary policy. The monetary sector is heavily influenced by real GDP shock, liquidity, and inflation shock. However, the monetary sector is only slightly affected by the decomposition of the variance of the exchange rate, which is very sensitive to the inflation shock. The study also indicates that the endogenous variables in the value of changes in interest rates and real exchange rate of rupiah will be close to convergence in the long term. The endogenous variables are more susceptible to changes in variables derived from domestic, such as the level of demand for domestic currency liquidity, compared to variables derived from international capital exposure. Thus, the value of the variable interest rate changes can be used to reduce the potential risks derived from domestic money demand shock.